The impact of infrastructure on Trade in Central Asia - Kamalbek Karymshakov; Burulcha Sulaimanova (Asian Development Bank Institute (ADBI), 2020)
The aim of this paper is to investigate the impact of infrastructure on trade in the case of Central Asian countries. Infrastructure is measured by the aspects of quality and quantity in three Central Asian countries - Kazakhstan, the Kyrgyz Republic, and Tajikistan. Trade flows are measured by the export and import volumes of each of these countries with their main trade partner countries. Empirical estimations are based on panel data for the period 2009-2017. Results show that both the quality and quantity of infrastructure in Central Asia have a positive impact on trade flows. However, estimations by country subsamples show that this effect varies by country. Given the general remote geographical location of Central Asian countries, the findings of this study indicate that a regional approach to the development of infrastructure is important and policy towards infrastructure development should be associated with a further regional economic integration process.
Keywords: N75; O18; O11; O53; 330; infrastructure; trade; Central Asia